Sustainable Enterprise Strategies for Optimizing Digital Stewardship: A Guide for Libraries, Archives, and Museums: by Angela Fritz, Lanham, Rowman & Littlefield Publishers, 2021, xv, 95 pp, £30 (paperback) ISBN 978-1-5381-4286-8. - MacGregor, Rachel (Archives & Records)
Angela Fritz's 'Sustainable Enterprise Strategies for Optimizing Digital Stewardship: A Guide for Libraries, Archives, and Museums' is a concise introduction and overview of the "digital asset management ecosystems" of GLAMs (galleries, libraries, archives and museums). This book will be of interest to anyone engaged in any form of digital curation activity although it is probably of most direct relevance to those working in a Higher Education environment which more closely mirrors the US situation which Fritz describes. Fritz provides a clear introduction in the first chapter to the digital asset management ecosystem concept and outlines the activities and responsibilities which form this.